Molecular biology of receptors and transporters : bacterial and glucose transporters - Friedlander, Martin; Mueckler, Michael (International review of cytology, 1992)
This multi-volume set within International Review of Cytology encompasses the recent advances in the understanding of structure-function relationships at the molecular level of receptors, transporters, and membrane proteins. Several diverse families of membrane receptors/proteins are discussed with respect to the molecular and cellular biology of their synthesis, assembly, turnover, and function. Included are such receptor superfamilies as G-proteins, immunoglobulins, ligand-gated receptors, interleukins, and tyrosine kinases as well as such transporter/protein families as pumps, ion channels.